The Relationship between Work Attitudes and Complaints of Musculoskeletal Pain in Laundry Workers - Chandrayana, Made Handy; Widnyana, Made; Antari, Ni Komang Ayu Juni; Saraswati, Ni Luh Putu Gita Karunia (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Musculoskeletal pain complaints are complaints in the form of mild to severe pain due to joints, ligaments, tendons, and skeletal muscles disorders. One of the factors causing complaints of musculoskeletal pain is ergonomics or work posture. Jobs that has a high risk of experiencing musculoskeletal pain complaints is the laundry business because the work activities are carried out with poor work postures such as twisting, bending and repeating for a long time. This research aims to understand the correlation between work postures and musculoskeletal pain complaints, especially in laundry workers. Methods: This research applies a cross sectional approach in analytical observational method. Sampling used purposive sampling technique with a sample of 47 people. Work posture was measured using the Ovako Work Posture Analysis System (OWAS), while musculoskeletal pain complaints were measured using the Nordic Body Map (NBM) questionnaire. Results: Based on the results of the non-parametric spearman rank analysis test, the value obtained was ρ=0.002 (ρ<0.05) and the correlation coefficient r=0.441. Conclusion: Based on the research results, it can be concluded that there is a significant relationship, sufficient strength, and the same direction between work postures and musculoskeletal pain complaints among laundry workers in Denpasar, Bali